2018
DOI: 10.1002/ijc.31906
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of a multiple biomarker panel to better predict prostate cancer metastasis after radical prostatectomy

Abstract: A plethora of individual candidate biomarkers for predicting biochemical relapse in localized prostate cancer (PCa) have been proposed. Combined biomarkers may improve prognostication, and ensuring validation against more clinically relevant endpoints are required. The Australian PCa Research Centre NSW has contributed to numerous studies of molecular biomarkers associated with biochemical relapse. In the current study, these biomarkers were re‐analyzed for biochemical relapse, metastatic relapse and PCa death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
(130 reference statements)
0
12
0
Order By: Relevance
“… 10 Recent work from our own group has shown that markers clearly associated with biochemical recurrence do not necessarily translate into markers of MR with more mature follow-up. 11 In this cohort, p53 nuclear accumulation correlates with biochemical recurrence after radical prostatectomy (RP) as described by our group more than 15 years ago. 12 With longer follow-up, we aimed to examine whether p53 could also predict MR and PC specific survival.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“… 10 Recent work from our own group has shown that markers clearly associated with biochemical recurrence do not necessarily translate into markers of MR with more mature follow-up. 11 In this cohort, p53 nuclear accumulation correlates with biochemical recurrence after radical prostatectomy (RP) as described by our group more than 15 years ago. 12 With longer follow-up, we aimed to examine whether p53 could also predict MR and PC specific survival.…”
Section: Introductionmentioning
confidence: 59%
“…Work from our group and others has shown that assessing p53 mutations on IHC from tissue microarrays (TMA) has not delivered the same results. 11 While TMA analysis is convenient and with appropriate sampling technique is suitable for most prostate cancer biomarkers, 21 our study has shown that p53 is an unusual biomarker that requires analysis of whole tissue sections and may be dismissed by the TMA method. The prognostic significance of the ‘clustering’ of p53-positive tumour nuclei is particularly relevant to the method of analysis.…”
Section: Discussionmentioning
confidence: 89%
“…While this may reflect limitations in the sample size of our cohorts, it also raises the possibility that lipidomic profiling may provide independent information regarding tumor biology and prognosis. Moreover, the associations we detected between lipid profiles and the TMPRSS2-ERG molecular subtype and Ki67 proliferative index are interesting observations that warrant further investigation in larger independent tissue cohorts, particularly in light of our recent report of Ki67 status in localized prostate cancer being a significant predictive biomarker of subsequent metastatic relapse(21).Despite differences in the breadth and scope of lipid classes measured, certain key cancerrelated changes in PL profile reported here support the findings of previous imaging-based studies, notably for altered abundance and/or elongation of PC and PI-based lipids and ceramides (reviewed in (2,22)). While the functional consequences of individual lipid changes remain to be elucidated, PI lipids are of fundamental importance in cancer cells as they form the membrane scaffold for kinase and phosphatase activity that supports oncogenic signaling.…”
mentioning
confidence: 58%
“…Importantly, the clinical outcome most often studied is BCR, defined by an increase in serum PSA levels post-RP. However, there is increasing evidence that BCR is not a sufficient indicator of progression to aggressive lethal disease, with metastatic relapse instead being the clinically relevant endpoint for predicting survival [ 72 , 73 ]. This requires long-term follow-up (≥15 years) for metastatic relapse and PCa death to manifest [ 16 ], which many study populations lack, thus reducing their ability to fully evaluate and assess molecular biomarkers of PCa prognosis.…”
Section: Current State Of Prognostic Methylated Biomarkersmentioning
confidence: 99%